Nuovi Metodi di visualizzazione geografica: l'approccio Focus+Glue+Context - Lupia, Flavio (GEOmedia, 2010)
New cartographic visualization methods: the Focus+Glue+Context approach Focus+Glue+Context is a new cartographic visualization method specifically designed to solve the fruition problems connected with the use of mobile devices and web mapping services. The objective of the F+G+C approach is to reduce users cognitive efforts when reading a map: to do so, the area of interest is ‘highlighted' in a lower and more detailed scale through a fisheye lens effect, while the sorrouding context, useful to the user to determine the items relationships in a map, is maintained on a higher scale.